EFFECTIVENESS OF GROUP GUIDANCE SERVICES USING VISUALIZATION TECHNIQUES (WILDED IMAGERY) TO REDUCE BODY IMAGE STRESS IN STUDENTS - Salsabila, Mutiara; Hasibuan, Ali Daud (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2025)
This research aims to describe the strategies employed by Guidance and Counseling teachers in addressing time constraints for classroom engagement at Dharma Utama Senior High School. Time limitations have become a significant challenge in delivering services, particularly in ensuring equitable attention for all students. This study adopts a qualitative approach using a case study method. The research subjects include Guidance and Counseling teachers, several students, and relevant subject teachers. Data were collected through in-depth interviews, observations, and documentation. he findings reveal that Guidance and Counseling teachers employ a variety of strategies, including the use of digital technology (such as social media and class WhatsApp groups), providing flexible services outside of regular class hours, and collaborating with homeroom and subject teachers. In addition, they optimize group guidance sessions and schedule classical (whole-class) counseling services. These strategies have proven to be quite effective in reaching a broader range of students despite time constraints. The study recommends stronger institutional support and better integration of guidance and counseling programs with other school activities to enhance the overall effectiveness of counseling services in the future.